A structured index describing the ease of disassembly for handcrafted product. Issue 1 (1st January 2019) - Francia, Daniela; Liverani, Alfredo; Donnici, Giampiero; Frizziero, Leonardo; Marinelli, Nicolò
Abstract: Both economic and environmental aspects significantly influence the design process since the early phases of preliminary design. The total Life Cycle Assessment (LCA) and the End of Life (EoL) of products have to be defined in the early design phases too but, for industrial products that are not feasible to automatic production, they are hard issues. However, the EoL of products can be assessed by evaluating the disassembly of joints assembling the product, even when the production process is subject to an important contribute of workmanship. In this paper, a useful method is proposed to analyze the disassembly plant of products, in order to optimize the design process in the early preliminary phases. The method quantitatively evaluates a Disassembly Index that describes the attitude of a product to be disassembled. A case study describes the disassembly attitude of structural subassemblies of a sailboat. In order to test the applicability of the model described to both manual and automated disassembly, a further application of the method is proposed on a Computer CPU. As result, the model demonstrated good sensitiveness to the testing of products quite different for dimensions, number of components, manufacturing processes and, in all cases, it quantified the disassembly easiness with good relevance.